Long-term care needs and hospitalization costs with long-term care insurance: a mixed-sectional study - Che, Tiantian; Li, Jia; Li, Jun; Chen, Xiaobo; Liao, Zangyi (Frontiers in Public Health, 2024)
Background：With the rapid aging of the population, the health needs of the older adult have increased significantly, resulting in the frequent occurrence of the "social hospitalisation" problem, which has led to a rapid increase in hospitalisation costs. This study investigates whether the "social hospitalisation problem" arising from the longterm care needs can be solved through the implementation of long-term care insurance, 2 thereby improving the overall health of the older adults and controlling the unreasonable increase in hospitalisation costs.The entropy theory was used as a conceptual model, based on data from the China Health and Retirement Longitudinal Study (CHARLS) in 2015 and 2018. The least-squares method was used to examine the relationship between long-term care needs and hospitalisation costs, and the role that long-term care insurance implementation plays in its path of influence.The results of this study indicated that long-term care needs would increase hospitalisation cost, which remained stable after a series of tests, such as replacing the core explanatory variables and introducing fixed effects. Through the intermediary effect test and mediated adjustment effect test, we found the action path of long-term care needs on hospitalisation costs. Long-term care needs increases hospitalisation costs through more hospitalisations. Long-term care insurance reduces hospitalisation costs. Its specific action path makes long-term care insurance reduce hospitalisation costs through a negative adjustment of the number of hospitalisations.To achieve fair and sustainable development of long-term care insurance, the following points should be achieved: First, long-term care insurance should consider the prevention in advance and expand the scope of participation and coverage; Second, long-term care insurance should consider the control in the event and set moderate levels of treatment payments; Third, long-term care insurance should consider post-supervision and explore appropriate payment methods.